Translation and creation in Zheng Zhenduo’s translation of “Apollo and Daphne” - Nico, Silvia (Sinología hispánica. China Studies Review, 2021)
Zheng Zhenduo, the Chinese translator, has made great contributions to the translation and introduction of Greek literature, and also put forward unique insights for the construction of Chinese translation theory. Based on Zheng Zhenduo 's translation theory, this article takes Zheng Zhenduo’s translation of Apollo and Daphne (Aipoluo yu Dafen), contained in Lian’ai de gushi (1929), a collection of Greek mythological stories that he selected and translated from English into Chinese as an example, it compares Zheng’s version and English version to analyze whether or not he remained consistent to his own translation theory when translating Greek mythological stories.